The Concept and measurement of quality of life in the frail elderly - Birren, James E. (Academic Press, 1991)
This work presents the first serious attempt to impose rigor on the definition and measurement of quality of life among the elderly. The book uses a conference to develop background but goes well beyond the meeting in terms of depth of reviews of the literature and of integration among the chapters.